VIABILITAS DAN VIGOR BENIH CENGKEH (Euegenia aromaticum L) PADA MEDIA PERKECAMBAHAN YANG BERBEDA - Purnawirawan, Sandi; Maemunah, Maemunah; Adelina, Enny (AGROTEKBIS, 2018)
The study aim wasto examine the viability and vigority of clover seedsat different growth media. The study used a Randomized Completelydesign at the first stage and a Randomized Block design at the second stage.Four different growth media as the treatments were consisted ofsawdust (m1), rice husk (m2), cocopeat (m3) and sand (m4). Each treatment had three replicates; therefore, there were12 experimental units in total. The data obtained was analyzed using analysis of variance. The results showed that 98.67% germination rate was stimulated by the cocopeat with100% growth potential, and time to germinate 97 days averagely better that the other treatments. The sawdust stimulated the first leaf areaof 3.33 cm2wider than the other treatments whereas the cocopeat produced hypothetical vigor index of 2.24higher than the other treatments. Key Words: Clove media,Viability, and Vigor